2017
DOI: 10.1111/jicd.12269
|View full text |Cite
|
Sign up to set email alerts
|

Gingival profiles in a select Asian cohort: A pilot study

Abstract: Aim: The aim of the present study was to determine the facial gingival profiles of teeth with a healthy periodontium in an Asian population. Methods:A total of 51 patients with a healthy periodontium were examined. Gingival thickness (GT) and gingival width (GW) were assessed at the maxillary and mandibular incisors to the first molars. GT was measured by transgingival probing (GT-TGP), and probe visibility through the marginal gingiva (GT-TRAN) was assessed. Results between groups (anterior and posterior, too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(104 citation statements)
references
References 28 publications
8
95
1
Order By: Relevance
“…The majority of studies found that GT varies within and between individuals. However, there is no major difference between overall GT in the maxilla and the mandible …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The majority of studies found that GT varies within and between individuals. However, there is no major difference between overall GT in the maxilla and the mandible …”
Section: Resultsmentioning
confidence: 97%
“…The characteristics and results of the included studies for this clinically focused question are presented in Table . All 25 included studies reported data for both KTW and GT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations